2005
DOI: 10.1093/fampra/cmi004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of ear, nose and throat problems in the community: results from a national cross-sectional postal survey in Scotland

Abstract: ENT problems occur frequently in the community, and most are managed without consulting medical services. Whilst reasonable for many problems, there are likely to be important groups in the community with ENT problems that might benefit from modern interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
192
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(212 citation statements)
references
References 15 publications
12
192
3
5
Order By: Relevance
“…[3][4][5][6][7] In the present study, as well as in previous studies, dizziness/vertigo was more common for women than for men in all age groups. 7,[9][10][11][12][13][14]29 However, women also have higher rates of sickness absence in general, 19,30,31 often explained by occupational differences. 19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] In the present study, as well as in previous studies, dizziness/vertigo was more common for women than for men in all age groups. 7,[9][10][11][12][13][14]29 However, women also have higher rates of sickness absence in general, 19,30,31 often explained by occupational differences. 19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…7,[9][10][11][12][13][14][15] Lifetime prevalence was estimated to be 30% in a German survey, 11 while a study from Scotland reported 21% vertigo, 29% unsteadiness, and 13% other types of dizziness. 10 In a sample of general practices in London, 24% reported patients with dizziness in the last month. 16 The studies differ, with unequal populations, different case definitions, and different measures of prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…4 Vertigo is among the most common reasons for a physician visit, with estimated lifetime prevalence between 20% and 30%. [5][6][7] An epidemiological study in France reported a considerably higher 1 year prevalence of 48.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many different forms of sound experiences are reported, a majority of patients describe the sound as buzzing, hissing, whistling, or ringing. Chronic tinnitus is a common health problem with a prevalence of 10-18% in the adult population (Gopinath, McMahon, Rochtchina, Karpa, & Mitchell, 2010;Hannaford, Simpson et al, 2005;Kuttila, Kuttila, Le Bell, Alanen, & Suonpää, 2005;Nondahl, Cruickshanks et al, 2010). However, only a small proportion of tinnitus patients, i.e., about 0.5 to 3% of the adult population, develop severe distress and experience impairment in everyday life (A.…”
Section: Introductionmentioning
confidence: 99%